Citizenship and Citizenship Education According to the Perspective of Non-Muslim Minorities in Turkey - (:unkn) unknown (My University, 2015)
0

The purpose of this research is to put forth the opinions and expectations of non-Muslim minorities concerning citizenship and citizenship education in Turkey. The research included three minority groups that have been officially recognized in Turkey: Orthodox Greeks, Armenians, and Jews. The qualitative method was adopted and the snowball sampling technique was used to select the participants. Semi-structured interviews were used as a data collection tool, and discussions based on the research questions were held during face-to-face interviews with the participants. The data accumulated during the semi-structured interviews was transcribed. After all the interviews had been written down, the texts were checked more than once and a holistic view was targeted concerning the issue. In the study, the content analysis method was used as a data analysis tool while notes from the interviews were analyzed categorically together with the questions that the participants had been asked. Considering the data gathered in this study, although the non-Muslim minorities had a certain number of suggestions and criticisms regarding citizenship and citizenship education policies that have been implemented in Turkey, these policies can be said to have generally reached a more positive point compared to the situation in the past.
Keywords: Eğitim, Eğitim Araştırmaları